DEVELOPMENT OF ANAEROBIC ENDURANCE IN WEIGHTLIFTERS THROUGH SPECIALIZED TRAINING EXERCISES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2026)
This scientific article examines the development of anaerobic endurance in weightlifters through the application of specialized training exercises, emphasizing the physiological, methodological, and performance-related aspects of anaerobic capacity in competitive weightlifting. Anaerobic endurance is analyzed as a key determinant of performance stability during repeated high-intensity efforts, particularly in training sessions and competitive environments characterized by maximal and near-maximal loads. The study applies a sport-science framework integrating exercise physiology, training theory, and performance analysis to identify how targeted special exercises influence anaerobic energy systems, neuromuscular efficiency, and fatigue resistance. The results demonstrate that systematically designed special exercises significantly enhance anaerobic endurance by improving phosphagen system efficiency, glycolytic tolerance, and recovery kinetics between high-intensity lifts. The findings contribute to evidence-based training optimization in weightlifting and provide practical recommendations for coaches and athletes aiming to improve competitive performance.